A Spatial Analysis of Land-use Land cover Pattern of Haryana, 1985–2023, using Geoinformatics tools. - Devender Sindhu (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Haryana is a small state in northern India that is making its mark in terms of economic development and increasing urbanization. The state's economy is transitioning from agriculture to industry, leading to a change in the state's land use and land cover. The dynamics of land use in a region are an indicator of economic change, but rapid land use change can affect environmental quality. Understanding land use and land cover is essential for determining policies related to sustainable regional development, land management, and environmental protection. This research paper employs modern geoinformation technology to analyse the land use and land cover changes in Haryana state from 1985 to 2023. This study has collected land use-related data from various satellite systems, such as Landsat 4 and 5, Sentinel-2 10 m regulation, IRS, LISS II and III, etc.The land use and land cover classes identified in different satellite data have been converted to the specific land use and land cover classes defined in the European Space Agency's Sentinel-2 data set, which has a resolution of 10 meters. The GIS software, QGIS, has processed all the data. Tables and maps represent the data presented in this study. The land use and land cover analysis of Haryana will help in making land use management and environmental protection decisions by providing an understanding of the magnitude of land use change.